2016
DOI: 10.7860/jcdr/2016/16949.7956
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Collision Tumour of Colon Leiomyosarcoma and Adenocarcinoma

Abstract: The colon is an exceedingly rare site of primary leiomyosarcoma and only a few cases have been published to date. Of the reported cases of collision tumours, collision tumours that specifically occurred in the colon have consisted of combinations of adenoma or adenocarcinoma with lymphomas or neuroendocrine tumours. Here, not only do we report a case of colon leiomyosarcoma, but we report, what is to our knowledge, the first case of collision tumour consisting of colon leiomyosarcoma and adenocarcinoma. Cause,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Duffy et al suggested that management options should be more aggressive concerning CT with major neuroendocrine components (51). Given their rare nature, CTs of the colon do not have standards for treatment and prognosis (52). All the patients in our study underwent surgical removal of their tumors.…”
Section: Discussionmentioning
confidence: 92%
“…Duffy et al suggested that management options should be more aggressive concerning CT with major neuroendocrine components (51). Given their rare nature, CTs of the colon do not have standards for treatment and prognosis (52). All the patients in our study underwent surgical removal of their tumors.…”
Section: Discussionmentioning
confidence: 92%
“…Collision of the two malignancies can occur between tumors originating in the same organ or between metastases from other sites [4]. In literature, collision tumors of the colon consist of a combination of adenoma or adenocarcinoma with lymphoma, neuroendocrine tumors or leiomyosarcoma [1][2][3]. To the best of our knowledge, this is the first case of a colon collision tumor composed of adenocarcinoma and IMT.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, collision tumors which have occurred in the colon consist of a combination of adenoma or adenocarcinoma with lymphoma, neuroendocrine tumors or leiomyosarcoma [1][2][3]. Here, we report the first case of a collision tumor composed of colon adenocarcinoma and an inflammatory myofibroblastic tumor (IMT).…”
Section: Introductionmentioning
confidence: 98%
“…There are only 11 publications describing collision tumors with pancreatic involvement with a collision between ductal adenocarcinoma and neuroendocrine tumor both of the pancreas being the most frequently described [1–11]. There are only 8 publications describing a collision tumor with any sarcoma involved [1017]. In those cases liposarcoma and leiomyosarcoma are the two most frequently mentioned entities.…”
Section: Discussionmentioning
confidence: 99%